2019
DOI: 10.1002/jbmr.3679
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alendronic Acid on Fracture Healing: A Multicenter Randomized Placebo-Controlled Trial

Abstract: There is a concern that bisphosphonates may impair fracture healing because of their inhibitory effects on bone turnover. Here we evaluated the effects of early bisphosphonate therapy on fracture healing and functional outcome following a fracture of the distal radius. The fracture and bisphosphonates (FAB) trial was a double-blind, randomized, placebo-controlled trial involving 15 trauma centers in the United Kingdom. We enrolled 421 bisphosphonate-naive patients aged !50 years with a radiographically confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
0
20
0
Order By: Relevance
“…The fracture and bisphosphonates (FAB) trial was a double-blind, randomized, placebo-controlled trial involving 15 trauma centers across the United Kingdom that enrolled 421 bisphosphonate-naive patients aged ≥50 years with a radiographically confirmed fracture of the distal radius and randomized them in a 1:1 ratio to receive alendronate 70 mg once weekly (n = 215) or placebo (n = 206) within 14 days of the fracture. Administration of this highly potent N-containing BP did not affect fracture healing or clinical parameters [49]. Collectively, these data would contradict the anecdotal claims of many veterinary practitioners that the BPs mechanism of action disrupts the natural bone healing process.…”
Section: That Is Important Information But What Are the Down Sides?mentioning
confidence: 78%
See 1 more Smart Citation
“…The fracture and bisphosphonates (FAB) trial was a double-blind, randomized, placebo-controlled trial involving 15 trauma centers across the United Kingdom that enrolled 421 bisphosphonate-naive patients aged ≥50 years with a radiographically confirmed fracture of the distal radius and randomized them in a 1:1 ratio to receive alendronate 70 mg once weekly (n = 215) or placebo (n = 206) within 14 days of the fracture. Administration of this highly potent N-containing BP did not affect fracture healing or clinical parameters [49]. Collectively, these data would contradict the anecdotal claims of many veterinary practitioners that the BPs mechanism of action disrupts the natural bone healing process.…”
Section: That Is Important Information But What Are the Down Sides?mentioning
confidence: 78%
“…1) treatment began within 90 days after hip fracture and no evidence of any delayed healing if treatment began within 2 weeks. More recently, the effects of early BP therapy on fracture healing and functional outcome following a fracture of the distal radius in osteoporotic patients was evaluated [49]. The fracture and bisphosphonates (FAB) trial was a double-blind, randomized, placebo-controlled trial involving 15 trauma centers across the United Kingdom that enrolled 421 bisphosphonate-naive patients aged ≥50 years with a radiographically confirmed fracture of the distal radius and randomized them in a 1:1 ratio to receive alendronate 70 mg once weekly (n = 215) or placebo (n = 206) within 14 days of the fracture.…”
Section: That Is Important Information But What Are the Down Sides?mentioning
confidence: 99%
“…(1) As Fung correctly states, the fracture and bisphosphonates (FAB) study showed that alendronic acid did not have a clinically important effect on fracture healing or patient-reported outcomes in patients who were bisphosphonate naïve for the previous 2 years. (1) As Fung correctly states, the fracture and bisphosphonates (FAB) study showed that alendronic acid did not have a clinically important effect on fracture healing or patient-reported outcomes in patients who were bisphosphonate naïve for the previous 2 years.…”
Section: To the Editormentioning
confidence: 99%
“…
We thank Dr Fung for his interest in our article that was recently published in JBMR. (1) As Fung correctly states, the fracture and bisphosphonates (FAB) study showed that alendronic acid did not have a clinically important effect on fracture healing or patient-reported outcomes in patients who were bisphosphonate naïve for the previous 2 years. We do not agree with the implication that the absence of data on biochemical markers of bone turnover in our study is a limitation.
…”
mentioning
confidence: 99%
“…To the Editor I read the article by Duckworth and colleagues (1) with great interest, especially as the JBMR June 2019 cover highlights "Alendronate Safe During Fracture Healing." The study shows that early use of alendronate, starting around 10 days after fracture, does not affect healing at 2, 4, 6, and 8 weeks and presumably also at 24 weeks.…”
mentioning
confidence: 99%